Preliminary Results From a Newly Established Behavioral Health Home: Early Identification of Glucose Metabolism Disorders in Individuals With Serious Mental Illness. (18th May 2015) - Maragakis, Alexandros; RachBeisel, Jill; Blount, Alexis
Objective: Individuals with serious mental illness (SMI) have higher rates of preventable diseases such as diabetes in comparison to the general population. While multifaceted, these high rates of preventable diseases in the population with SMI may be partially attributed to limited access to primary care. A new program, the Behavioral Health Home (BHH), which allows for the delivery of somatic care coordination and population-based care, may provide this population with the much needed somatic coordination and education it requires. Methods: The impact of the population-based health management program of the BHH identification and severity rating of glucose metabolism disorders was assessed during the initial 10 months of the BHH. Results: Multiple patients were identified who either were not having hemoglobin A1c (HbA1c) levels drawn per recommended guidelines for individuals prescribed antipsychotic medications or were within diabetic range but did not have a diagnosis of diabetes. Mixed results occurred in regard to patients' HbA1c levels while engaging in the BHH. Conclusion: This case study provides some initial evidence for the utility of the BHH in regard to identifying patients who need preventive care.